Conflict on Religion in Indonesia - Daus, Firdaus (Faculty of Social and Political Sciences University of Bangka Belitung, 2023)
The friction between these divergent beliefs has been ongoing for years and has been failed by the state. The state, in this case, the government in the center or the region, has the obligation to perform its role and the obligation to protect the rights of citizens in their religious and/or religious beliefs.